2002
DOI: 10.1177/089198870201500105
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between the Apolipoprotein E Genotype and Depression in Alzheimer's Disease

Abstract: The epsilon4 allele of apolipoprotein (apo E) is one of the risk factors for late-onset Alzheimer's disease (AD). We evaluated the association between apo E genotypes and depression in patients with AD. A psychiatrist interviewed all patients and their caregivers for depression using a Chinese version of the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Third Edition, Revised, and for the severity of depression using the Hamilton Depression Rating Scale (HDRS). Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…A recent study suggested that depression and APOE ε4 genotype may be higher in women with AD but not in men (Muller-Thomsen et al, 2002). Despite these findings supporting an association between APOE and depression, several other published studies have not supported the notion that APOE ε4 genotype influences depression in AD (Liu et al, 2002;Scarmeas, et al, 2002;Craig et al, 2005).…”
Section: Introductionmentioning
confidence: 38%
See 3 more Smart Citations
“…A recent study suggested that depression and APOE ε4 genotype may be higher in women with AD but not in men (Muller-Thomsen et al, 2002). Despite these findings supporting an association between APOE and depression, several other published studies have not supported the notion that APOE ε4 genotype influences depression in AD (Liu et al, 2002;Scarmeas, et al, 2002;Craig et al, 2005).…”
Section: Introductionmentioning
confidence: 38%
“…A recent study suggested that depression and APOE ε4 genotype may be higher in women with AD but not in men (Muller-Thomsen et al, 2002). Despite these findings supporting an association between APOE and depression, several other published studies have not supported the notion that APOE ε4 genotype influences depression in AD (Liu et al, 2002;Scarmeas, et al, 2002;Craig et al, 2005).Discrepant findings may be due to a number of factors including small sample sizes, differences in sample compositions (e.g., general "dementia" groups versus strictly diagnosed patients with "probable AD"), and the use of very brief, wide-ranging, or unstructured psychopathology inventories. In addition, others have shown trends toward association between APOE genotype and depression but have rendered conclusions of no relationship.…”
mentioning
confidence: 46%
See 2 more Smart Citations
“…However, some work suggested that the APOE epsilon4 genotype may be overrepresented in AD depressed patients or among depressed women with AD [42,43]. Other researchers have not confirmed an additional role for APOE in conferring risk to ADrelated depression [44,45].…”
Section: Genetic Basis Of Depression In Alzheimer Diseasementioning
confidence: 94%